Psychosocial variables influencing depression tendency and quality of life of stroke (2013)
Adaptation to stroke may require complex long-term change in stroke patients’ lives. This study examined the psychosocial variables influencing depression tendency and quality of life among stroke patients. The independent variables are personality traits and demographic variables while the dependent variables are depression and quality of life. Data were collected on stroke patients using a cross-sectional design and standardized questionnaires. A total of 112 stroke survivors took part in the study in which 57 (50.9%) were males and 55 (49.1%) were females with a mean age of 50.63 and standard deviation of 8.657 with age ranging from 30 to 74 years. Four hypotheses were tested using the multiple regression analysis and t-test for independent measures. The first hypothesis shows that jointly, agreeableness, conscientiousness, extraversion, openness to experience and neuroticism significantly predicted Quality of life among the stroke patients in the study. The result revealed that conscientiousness and extraversion independently predicts Quality of life of Stroke patients while agreeableness, openness to experience and neuroticism did not independently predict Quality of life. The second hypothesis predicted that agreeableness, conscientiousness, extraversion, openness to experience and neuroticism significantly and jointly predicted depression among stroke patients. The result also demonstrated that there was independent influence of agreeableness, openness to experience and neuroticism on the level of depression in Stroke patients while conscientiousness and extraversion did not independently predict depression among stroke patients. The result shows that male stroke patients were more depressed than female stroke patients. However, female stroke patients have better quality of life than male stroke patients. The results were discussed exhaustively in relation to the existing literature and it was concluded that efforts should be made to consider personality factors such as agreeableness, openness to experience, neuroticism, conscientiousness and extraversion as a prerequisite in conducting rehabilitation programs among stroke patients this will go a long way to boost their recovery and increase their level of wellbeing. Rehabilitation programs for this group of people (stroke survivors) would be more effective if they are based upon a holistic approach